Laboratory study on the life history of bloom-forming Ulva prolifera in the Yellow Sea. (20th September 2015) - Liu, Qing; Yu, Ren-Cheng; Yan, Tian; Zhang, Qing-Chun; Zhou, Ming-Jiang
Abstract: Ulva prolifera is the major causative species of large-scale green tides in the Yellow Sea (YS) of China. It has complex life cycles and multiple reproduction modes, such as parthenogenesis, a reproduction mode previously reported in many Ulva species with different consequences. However, there is little knowledge on the consequences of parthenogenesis in the following generations of U. prolifera . In this study, four strains of bloom-forming U. prolifera isolated from the YS were observed for multiple successive generations in the laboratory for approximately 2 years, and the type of thalli developed directly from unfertilized gametes and their following generations was determined by the zoids they produced. Among the four strains we examined, the gametes of two strains developed into parthenosporophytes (PS), followed by alternative generations of gametophytes (G) and parthenosporophytes. The other two strains, however, exhibited repeating generations of gametophyte, and then reverted to the isomorphic PS/G life cycle in February, 2013, after 8 gametophytic generations. The findings in this study suggest that parthenogenetic reproduction is a common feature of bloom-forming U. prolifera in the YS, which is likely to promote the rapid proliferation of U. prolifera population and to maintain its unique features. However, more detailed investigations are required to elucidate the role of parthenogenesis in the formation of green tides of U. prolifera in the YS. Graphical abstract: Highlights: Parthenogenesis could play important roles in the formation of green tides. Consequences of parthenogenesis in four Ulva prolifera strains were studied. Parthenogenesis is common in U. prolifera but their consequences are different. Two strains showed cycles of alternative parthenosporophyte and gametophyte. Two strains repeated gametophyte generations but reverted to PS/G cycles later.